Cadmium-Induced Disruption in 24-h Expression of Clock and Redox Enzyme Genes in Rat Medial Basal Hypothalamus: Prevention by Melatonin - Jiménez Ortega, Vanesa; Cano-Barquilla, Pilar; Scacchi, Pablo A.; Cardinali, Daniel P.; Esquifino, Ana I. (Frontiers in Neurology, 2011)
In a previous study we reported that a low daily p.o. dose of cadmium (Cd) disrupted the circadian expression of clock and redox enzyme genes in rat medial basal hypothalamus (MBH). To assess whether melatonin could counteract Cd activity, male Wistar rats (45 days of age) received CdCl2 (5 ppm) and melatonin (3 μg/mL) or vehicle (0.015 % ethanol) in drinking water. Groups of animals receiving melatonin or vehicle alone were also included. After 1 month, MBH mRNA levels were measured by real-time PCR analysis at 6 time intervals in a 24-h cycle. In control MBH Bmal1 expression peaked at early scotophase, Per1 expression at late afternoon and Per2 and Cry2 expression at mid-scotophase, whereas neither Clock nor Cry1 expression showed significant 24-h variations. This pattern was significantly disrupted (Clock, Bmal1) or changed in phase (Per1, Per2, Cry2) by CdCl2 while melatonin counteracted the changes brought about by Cd on Per1 expression only. In animals receiving melatonin alone the 24-h pattern of MBH Per2 and Cry2 expression was disrupted. CdCl2 disrupted the 24-h rhythmicity of Cu/Zn- and Mn-superoxide dismutase (SOD), nitric oxide synthase (NOS)-1, NOS-2, heme oxygenase (HO)-1 and HO-2 gene expression, most of the effects being counteracted by melatonin. In particular, the co-administration of melatonin and CdCl2 increased Cu/Zn-SOD gene expression and decreased that of glutathione peroxidase (GPx), glutathione reductase (GSR) and HO-2. In animals receiving melatonin alone, significant increases in mean Cu/Zn and Mn-SOD gene expression, and decreases in that of GPx, GSR, NOS-1, NOS-2, HO-1 and HO-2, were found. The results indicate that the interfering effect of melatonin on the activity of a low dose of CdCl2 on MBH clock and redox enzyme genes is mainly exerted at the level of redox enzyme gene expression.